Moderating role of Family System on the Relationship between Dark Triad Personality Traits and Use of Self Presentation Tactics among University Students - Shaheen, Habiba; Saeed, Hareem; Rashid, Samina (Annals of Human and Social Sciences, 2025)
The goal of the current study was to asses the moderating role of the family system in the relationship between the use of assertive self-presentation tactics and dark triad personality traits among university students. The Self-Presentation Theory posits that individuals engage in self-presentation to shape others’ perceptions, gain social acceptance, and achieve desired outcomes. Keeping in view current study focused on investigating the relationship between these two variales as well as to examine moderating role of family system on these variables. Using purposive sampling technique, 400 college students (n =252 females and n =148 males) between the ages of 18 and 25 were selected from Wah Cantt and Islamabad.Data was gathered using the Self-presentation techniques scale (SPTS) and the Short Dark Triad (SD3), which measures dark triad personality traits and self-presentation style. Results of the present study illustrated a significant positive correlation between dark triad and all assertive self-presentation tactics and family system moderated this relationship , males score higher than females in exhibiting dark triad traits and in the usage of assertive self-presentation tactics. Study results can be helpful for professionals to screen out Dark Triad behaviors, thus facilitating early intervention and effective treatment plans. Future researchers should focus on longitudinal studies and larger sample size for diversity.